Solar photovoltaic energy - Labouret, Anne; Villoz, Michel (The Institution of Engineering and Technology, 2010)
This professional manual on photovoltaic energy gives designers, installers and managers the tools and methods for: the effective writing of technical reports; and calculating, installing and maintaining the necessary components (solar panels, batteries, charge controllers, conductors, etc.) with the aim of designing and putting in place photovoltaic installations adapted to specific needs, conserving energy and taking into account both the opportunities and limits of this new energy. It gives a detailed account of the physical phenomena (conversion and storage of solar energy) as well as the available technology and the technology currently in development. This edition includes a number of updates on the economical and technical aspects of this energy, as well as exploring the possibilities of connecting it to a network of photovoltaic systems. This book is an essential tool for technicians and engineers involved in the field of solar energy (installers and users), as well as professional researchers. It will also be a useful reference for engineering students, including those in electronic engineering.